2011
DOI: 10.1128/jvi.00555-11
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Respiratory Syncytial Virus Fusion Glycoprotein in the Postfusion Conformation Reveals Preservation of Neutralizing Epitopes

Abstract: Respiratory syncytial virus (RSV) invades host cells via a type I fusion (F) glycoprotein that undergoes dramatic structural rearrangements during the fusion process. Neutralizing monoclonal antibodies, such as 101F, palivizumab, and motavizumab, target two major antigenic sites on the RSV F glycoprotein. The structures of these sites as peptide complexes with motavizumab and 101F have been previously determined, but a structure for the trimeric RSV F glycoprotein ectodomain has remained elusive. To address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
427
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 354 publications
(448 citation statements)
references
References 46 publications
19
427
1
1
Order By: Relevance
“…In addition, HRSV contains a small hydrophobic protein, SH, of unclear function and proteins of cellular origin, such as actin and chaperones (12). The RNP and F have been analyzed using 3D-EM and X-ray crystallography (13,14).HRSV particles are pleomorphic with both spherical and filamentous particles of different sizes (15). Early electron microscopy studies showed the presence of a helical protein layer under the membrane of filamentous HRSV (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HRSV contains a small hydrophobic protein, SH, of unclear function and proteins of cellular origin, such as actin and chaperones (12). The RNP and F have been analyzed using 3D-EM and X-ray crystallography (13,14).HRSV particles are pleomorphic with both spherical and filamentous particles of different sizes (15). Early electron microscopy studies showed the presence of a helical protein layer under the membrane of filamentous HRSV (15).…”
mentioning
confidence: 99%
“…In addition, HRSV contains a small hydrophobic protein, SH, of unclear function and proteins of cellular origin, such as actin and chaperones (12). The RNP and F have been analyzed using 3D-EM and X-ray crystallography (13,14).…”
mentioning
confidence: 99%
“… Partial amino acid sequences of the hMPV F (blue) and hRSV F (red) antigenic site II (Toiron et al , 1996; Lopez et al , 1998; McLellan et al , 2011b). Partial sequences of the F‐415 and F‐416 chimeras are color coded to indicate the origin of their antigenic site II residues.…”
Section: Resultsmentioning
confidence: 99%
“…pRB21/postfusion hRSV F (Post‐hRSV F): This plasmid encodes residues 1–524 of the hRSV F ectodomain (Long strain) with a deletion of the fusion peptide (residues 137–146) to avoid aggregation (McLellan et al , 2011b; Palomo et al , 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation